Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1982
DOI: 10.1175/1520-0477-63.7.739
|View full text |Cite
|
Sign up to set email alerts
|

Have Precipitation Forecasts Improved?

Abstract: Twelve years of precipitation forecasts made at National Weather Service forecast offices have been evaluated with a view to determining accuracy trends. Relative precipitation frequency, which proved to be negatively correlated to forecast accuracy, accounted for generally more than 80% of the variance. Winter forecasts were better than summer forecasts, and accuracy differed insignificantly among the eastern, southern, central, and western regions. After the contribution of relative precipitation frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1983
1983
1996
1996

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 1 publication
1
10
0
Order By: Relevance
“…Bosart (1983), for the SUNYA equivalent of our 7MIN and PP forecasts, shows averaged loss of skill at the annual rate of eight tenths of a percent (from the regression coefficients in his figures 1 and 2) per year. Ramage (1982), in a study of NWS 12-h forecasts of precipitation probability up to 36-h range, found evidence of increasing skill only in the eastern and central regions in winter and there at an annual rate of only one or two tenths of a percent. In a study designed to see whether Ramage's pessimism would withstand reexamination of the data and extension in time, Glahn (1985) considered these NWS forecasts from 1967 to 1982.…”
Section: Trends With Timementioning
confidence: 98%
See 2 more Smart Citations
“…Bosart (1983), for the SUNYA equivalent of our 7MIN and PP forecasts, shows averaged loss of skill at the annual rate of eight tenths of a percent (from the regression coefficients in his figures 1 and 2) per year. Ramage (1982), in a study of NWS 12-h forecasts of precipitation probability up to 36-h range, found evidence of increasing skill only in the eastern and central regions in winter and there at an annual rate of only one or two tenths of a percent. In a study designed to see whether Ramage's pessimism would withstand reexamination of the data and extension in time, Glahn (1985) considered these NWS forecasts from 1967 to 1982.…”
Section: Trends With Timementioning
confidence: 98%
“…Why is more expected of us? Could it be, as Ramage (1982) has so succinctly put it, that "the great technological developments of the duodecennium have apparently belied the expectations of their proponents"?…”
Section: Concluding Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…2.1a). However, in recent years the skill of forecasts of precipitation occurrence has improved little (Shuman, 1978), if at all (Ramage, 1982), and the skill of quantitative precipitation forecasts has not improved ( Fig. …”
Section: * Current Nw Practicementioning
confidence: 99%
“…
Ramage (1982) has presented evidence, based on extensive verification data for precipitation forecasts, that the percent of correct forecasts decreases approximately linearly with increasing precipitation frequency. However, only a limited range of precipitation frequency was examined in his study.
…”
mentioning
confidence: 99%